PELATIHAN PENERAPAN METODE SUGGESTOPEDIA DALAM PEMBELAJARAN GRAMMAR BAHASA INGGRIS DI SMKN 1 BATAM - Afriana Afriana; Nafdi Irawan; Sipri Hanus Tewarat; Zia Hisni Mubarak; Yevis Haritsyah (ASOSIASI IDEBAHASA KEPRI, 2026)
This community service activity aims to implement the Suggestopedia method in teaching English grammar to eleventh-grade students of the Industrial Automation Department at SMKN 1 Batam. Grammar learning is often perceived as difficult and monotonous, which reduces students’ motivation and participation. Therefore, the Suggestopedia method was selected because it emphasizes a relaxed learning atmosphere, positive suggestion, music, and interactive activities to minimize students’ anxiety in learning a foreign language. This program was conducted through teaching practice involving interactive explanations, games, songs, and online quizzes. The results indicate that students showed higher enthusiasm, active participation, and better understanding of basic tenses, including simple present, simple past, simple future, and present continuous tense. The implementation of the Suggestopedia method contributes positively to improving students’ motivation and confidence in using English. This activity highlights the importance of innovative teaching methods in enhancing the quality of English grammar learning at vocational schools.